LID LOCKING STRUCTURE - TERADA AKIHIRO (2022)
To prevent a lid body from easily removed by travel of a vehicle.SOLUTION: A lid locking structure includes a locking fitting 30 for attaching/detaching a lid body 9 to/from a receiving frame D, in which the locking fitting 30 includes: a locking body part 34 projecting downward relative to the lid body 9; a hook 37 that is arranged to a side close to a lower end of the locking body part 34 and is arranged at a locking position and an unlocking position by rotation around a shaft center of the locking body part 34; a restriction/permission body 35 for restricting rotation around the shaft center of the locking body part 34 at the locking position X1 by the hook 37; and pressing means 36 for energizing the restriction/permission body 35 to the side of the regulation position Y1. The lid body 9 includes a regulation part 50 that is engaged with the restriction/permission body 35 at the regulation position Y1 and regulates rotation of the lid body 9.SELECTED DRAWING: Figure 6 【課題】 車の走行等によって容易に蓋体が外れないようにする。【解決手段】 受枠Ｄに対する蓋体９の着脱を行う施錠具３０を備え、施錠具３０は、蓋体９に対し下方に突出した施錠本体部３４と、施錠本体部３４の下端寄りに配置されて施錠本体部３４の軸心周りの回動によって施錠位置および解錠位置に配置されるフック３７と、フック３７により施錠位置Ｘ１にある施錠本体部３４の軸心周りの回動を規制する規制許容本体３５と、規制許容本体３５を規制位置Ｙ１の方へ付勢する押圧手段３６とを備え、蓋体９は、規制位置Ｙ１の規制許容本体３５に係止しての蓋体９の回動を規制する規制部５０を備える。【選択図】 図６